2012
DOI: 10.1194/jlr.m019430
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of glucose and oleate metabolism to cardiac function in lipin-1 deficient (fld) mice

Abstract: of cardiac ATP production ( 1 ). FAs are also incorporated into triacylglycerol (TG), which is stored in lipid droplets. Cardiac TG turnover is rapid ( 2 ) and FAs released from TG can contribute up to 10-20% of ATP production ( 3 ). Plasma FA and TG levels rise in insulin resistance and diabetes ( 4, 5 ), and cardiac FA utilization can increase to supply as much as 90% of ATP ( 6, 7 ). Despite this increase in FAO, FA uptake can exceed the ability of the heart to utilize FAs, leading to excess accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 80 publications
2
51
1
Order By: Relevance
“…3). Similarly, Kok et al (46) did not find significant differences in ERK1/2 phosphorylation in fld hearts, suggesting that the effect of phosphatidic acid on ERK phosphorylation may be tissuespecific. ERK1/2 is required for the transcriptional activation of D-type cyclins and plays a fundamental role in the G 0 /G 1 to the S phase transition.…”
Section: Volume 290 • Number 39 • September 25 2015mentioning
confidence: 89%
“…3). Similarly, Kok et al (46) did not find significant differences in ERK1/2 phosphorylation in fld hearts, suggesting that the effect of phosphatidic acid on ERK phosphorylation may be tissuespecific. ERK1/2 is required for the transcriptional activation of D-type cyclins and plays a fundamental role in the G 0 /G 1 to the S phase transition.…”
Section: Volume 290 • Number 39 • September 25 2015mentioning
confidence: 89%
“…However, animals die within 24 h of treatment, and no differences between wt or fld groups are appreciated. It should be noted in this regard that recent work has shown that fld mice exhibit cardiac dysfunction in vivo (40). Such a defect, together with the well-described cardiac dysfunction induced by high levels of LPS, could explain why fld mice are not protected against high LPS doses (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In lipin-1-deficient mice, the accumulation of the PAP enzyme substrate, PA, in Schwann cells and adipose tissue has been implicated in the pathogenesis of peripheral neuropathy and lipodystrophy, respectively (11,30). This raised the possibility that PA accumulation in lipin-2-KO cerebellum as the mice age contributes to the ataxia.…”
Section: Lipin-2-deficient Mice Develop Ataxia Associated With Age-dementioning
confidence: 99%